Phoneme -Grapheme decoding in Phonics-Based Instruction of English as a Second Language at an Italian High School: A Randomised Controlled Trial (GIST – Education and Learning Research Journal, 2018)
Recent neurological breakthroughs in our understanding of the Critical Period Hypothesis and prosody may suggest strategies on how phonics instruction could improve L2 language learning and in particular phoneme/grapheme decoding. We therefore conducted a randomised controlled-trial on the application of prosody and phonics techniques, to improve phoneme-grapheme decoding, to test these findings on a typical late high school cohort of Italians. A trial group of 24, 17-18 year-olds followed a short 10-week, 20-hour trial course and were compared to a control (14 students) preparing for the Cambridge First Certificate exam. The trial group were given phoneme/grapheme decoding material and event-related-potential reinforcement in substitution of traditional exam practice, taught from a current textbook and web-site material. Results showed that the trial-group significantly improved in both orthography (p=0.048) and pronunciation (p=0.000), in particular in the long vowel and digraph categories. Furthermore, they significantly improved in a shortened interview category (p=0.024), for lexis, discourse and pronunciation. Due to the trial’s small size, we concentrated on reducing type 2 statistical errors to a minimum. We believe that our results confirmed the neurological findings of the use of prosody in TESOL and confirmed the validity of phonics techniques for L2 teaching. We also consider that the results are sufficiently robust to warrant a full-sized trial of phonics and prosody as a valid TESOL teaching technique
Keywords: Critical Period Hypothesis; prosody; phonics; orthography; pronunciation; phoneme-grapheme decoding; TESOL